Cross Cultural Adaptation and Validation of the "Patient-Generated Subjective Global Assessment (PG-SGA)" for Nutritional Status Assessment of Cancer Patients - Jalil Shahabbasi (Taṣvīr-i salāmat, 2018)
Background and Objectives: Because of the nature of the disease, many patients with cancer are at higher risk of malnutrition. This may result in a remarkable reduction in the quality of life and poor prognosis. The Patient-Generated Subjective Global Assessment (PG-SGA) is a standard tool for assessment of the nutritional status of cancer patients in both research and clinical settings which enables screening and assessing nutritional status of cancer patients. The aim of this study was cross culturally adaption and validation of PG-SGA in Persian for using in Iranian patients. Material and Methods: The guidelines of International Society for Pharmacoeconomics and Outcomes Research (ISPOR) was used for the cross cultural adaption of PG-SGA. The measures for content, face and construct validity using exploratory factor analysis were investigated. Tool relevancy for data analysis was calculated by intra class correlation coefficient and internal consistency using Cronbach's Alpha coefficient. Results: The accessibility rate of PG-SGA was 100%, and content validity in terms of its ease of understanding, difficulty, and relevancy were found 0.94, 0.84 and 0.92, respectively. The face validity was 100%. The reliability of the tool using test-retest was calculated 0.84. An internal consistency of 0.60 was obtained using Cronbach's Alpha, and a value of more than 0.60 for structural validity was achieved (p Conclusion: The Persian version of PG-SGA is an easy to understand tool. It may be used to assess nutritional problems in cancer patients in Iran.